Preoperative opioid use and complications following total joint replacement: a protocol for a systematic review and meta-analysis. Issue 6 (16th June 2020) - Shadbolt, Cade; Gould, Daniel; Camacho, Ximena; Knight, Josh; Rele, Siddharth; Thuraisingam, Sharmala; Zhang, Yuting; Dowsey, Michelle M; Choong, Peter FM
Abstract : Introduction: Mounting evidence now indicates that preoperative opioid use is associated with an array of complications following total joint replacement (TJR). However, evidence of these risks remains fragmented. A comprehensive and well-integrated understanding of this body of evidence is necessary to appropriately inform treatment decisions, the allocation of limited healthcare resources, and the direction of future clinical research. The proposed systematic review and meta-analysis aims to identify and synthesise the available evidence of an association between opioid use prior to TJR and postoperative complications, categorised by complication type. Methods and analysis: We will search MEDLINE, EMBASE, CINAHL, PsycINFO, and Web of Science from inception to April 2020. Observational and experimental studies that compare preoperative opioid users who have undergone elective TJR to opioid naïve TJR patients will be included. The primary outcomes will be postoperative complications, which will be categorised as either mortality, morbidity, or joint-related complications. The secondary outcomes will be persistent postoperative opioid use, readmission, and length of stay. Individual study quality will be assessed using the relevant NIH–NHLBI study quality assessment tools. Findings will be reported in narrative and tabular form, and, where possible, odds ratios (dichotomous outcomes) or standardised mean differences (continuous outcomes) will be reported with 95% confidence intervals. Where appropriate, random effect meta-analyses will be conducted for each outcome, and heterogeneity will be quantified using the I 2 statistic and Cochran's Q test. This study will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analyses Of Observational Studies in Epidemiology (MOOSE) guidelines. Ethics and dissemination: Ethics approval will not be required as no primary or private data are being collected. Findings will be disseminated through peer-reviewed publication and presentation at academic conferences. PROSPERO registration number: CRD42020153047.